Religion, Law, and the Dynamics of Intellectual Transmission: Weimar Jurisprudence among Religious Socialists in Israel. (May 2022) - Kaye, Alexander
Abstract : Weimar legal philosophy enjoyed a surprising prominence in religious kibbutzim. These were communities, established in Palestine/Israel, whose members attempted to create revolutionary utopian societies organized around the principles of socialism, Jewish nationalism, and Orthodox Jewish law. The kibbutzim existed under the shadow of a double crisis: the economic and social upheaval of the era, and the intellectual and spiritual challenge of synthesizing the diverse world views to which they were committed. Remarkably, the legal philosophy developed by the jurists of Weimar Germany – Hans Kelsen and Gustav Radbruch in particular – provided an intellectual framework by which the thinkers of the religious kibbutz navigated these crises.This article identifies references to Weimar jurisprudence in the discourse of the religious kibbutz, and addresses how and why kibbutz thinkers used it to think through issues that were so far removed from interwar Germany. It also expands our understanding of legal and historical phenomena in general, beyond the confines of the study of Israel or Judaism. It explores the ways that jurisprudence may be employed in religious and social thought. It also demonstrates how legal ideas flow along paths of immigration and intellectual exchange, how they can be applied by diverse actors in very different social circumstances, and how law and legal transplants operate, even outside the context of the state.